Padrões setoriais da inovação tecnológica na indústria brasileira: uma análise de Cluster a partir da PINTEC - Castro, Daniela Fernandes de (2010)
This research aims at analyzing the pattern of technical change in Brazilian industry of the triennium 2003-2005, from the Pesquisa de Inovação Tecnologica - PINTEC 2005 according to international taxonomy created by Keith Pavitt in 1984. The research procedure used was a literature search, based on the economic literature neoschumpeterian approach and also works that presented an overview of the industry standard for technological innovation in Brazil by PINTEC. The theoretical framework was adopted the Taxonomy Sectoral Patterns of Technological Innovation. The primary data source used was the Pesquisa de Inovação Tecnológica - PINTEC, published by the Instituto Brasileiro de Geografia e Estatística - IBGE. As a tool for empirical analysis, we used a multivariate analysis of cluster. The work is divided into four chapters, besides the introduction and closing remarks. The first chapter presents a literature review of key concepts surrounding the subject innovation. In the second chapter, we present some results of PINTEC 2005 and an overview of the work on pattern of technical change in Brazilian industry according to various methods of sector classification. The third chapter is devoted to discussion of the methodology adopted in the dissertation. In the last chapter, we present and analyze the results, which enable to characterize the sectorial pattern of the innovation in Brazil on the Pavitt´s taxonomy. As a conclusion and answer our search problem, we classify some twenty-three sectors of Brazilian industry along the lines, or rather, seventy-seven percent of the thirty sectors studied, the rest of the sectors could not be classified. No sector of the Brazilian showed a clear pattern of technological innovation Pavitt´s type of Specialized Suppliers. Anyway, we understand that the Brazilian industrial sectors show a pattern of technological innovation aligned with the Pavitt´s taxonomy